Leadership, Work Motivation, and Work Discipline on Job Satisfaction and Teacher Performance of Dharma Loka Elementary School Pekanbaru - Andrianto, Sukrisna; Komardi, Dadi; Priyono, Priyono (Journal of Applied Business and Technology, 2023)
This study aims to determine and analyze the influence of leadership, work motivation, and work discipline on job satisfaction and teacher performance at Dharma Loka Elementary School Pekanbaru. The questionnaire as data collector from 42 respondents proportionally to all educators/teachers of SD Dharma Loka, was tested using Path Analysis (Path Smart PLS). The test results show, Leadership has a positive and insignificant effect on Job Satisfaction, Work Motivation has a positive and significant effect on Job Satisfaction, Work Discipline has a positive and insignificant effect on Job Satisfaction, and Leadership has a positive and insignificant effect on Teacher Performance, Work Motivation has a positive effect and not significant on teacher performance, work discipline has a positive and insignificant effect on teacher performance and job satisfaction has a positive and insignificant effect on teacher performance. Leadership, Work Motivation, and Work Discipline as independent variables Job Satisfaction, Teacher Performance as the dependent variable.